Analisis Bauran Pemasaran Pada Keputusan Pembelian BSI Hasanah Card (Studi Pada Bank Syariah Indonesia Cabang Ahmad Yani Semarang) - Fanie Ardianti (Jurnal Ilmiah Ekonomi Islam, 2022)
Bank Syariah Indonesia as one of the new players as a financial service provider has special challenges in carrying out marketing activities. One of the tools used in determining the marketing strategy is the marketing mix. The marketing mix includes product, price, place, promotion, people, physical evidence, process. This study aims to analyze the factors that can increase purchasing decisions on consumers who are applying for a BSI Hasanah Card at the Ahmad Yani Branch Office, Semarang City. The sample of this study amounted to 120 respondents who responded to the questionnaire given by the researcher. Determination of the sample using non-probability sampling with convenience sampling technique, namely anyone who can provide information related to the research subject that is easily accessible and easy to find. The specified sample size refers to Hair et al. (2014) A good sample size should be 100 or more. In this study, the respondents were consumers who were applying for a BSI Hasanah Card at the Ahmad Yani Branch office in Semarang. The tool used to analyze the data is SPSS 24 with multiple regression method.The results showed that of the seven proposed hypotheses, there were 5 accepted hypotheses and 2 rejected hypotheses. The factors that have a significantly positive effect are Products, Prices, Promotions, People, Processes on Purchase Decisions. Then the one that does not have a significant effect is the Place and Physical Evidence on the Purchase Decision.